The effectiveness of smart board in enhancing grade 6 technology teachers' creativity at Nkomazi East Circuit in Mpumalanga Province, South Africa - Ndwandwe, Khanyisile Precious (My University, 2024)
Creativity is very important in education as it makes learners to fully concentrate throughout the learning and teaching process. Hence, the purpose of this study was to explore the effectiveness of a smart board in enhancing Grade 6 Technology teachers’ creativity at Nkomazi East Circuit in Mpumalanga Province. The theory of creativity was used as a lens in the study, and the 9E instructional model was used to guide and understand classroom activities. The qualitative research approach and the case study design were used to gather and analyse data. Data collection involved both non-participant observations and semi-structured interviews. Four schools with smart boards were purposively sampled. The participants of the study included four Technology teachers and eight learners. All four teachers were interviewed and observed teaching using the smart boards, while the eight learners participated in interviews. To analyse the data, the study used deductive content analysis. The findings of the study revealed that smart boards are effective in enhancing teachers’ creativity, as they were able to make their lessons more interesting, exciting and effective, and developed learners’ creative thinking skills. They could access the internet to search for online resources which include but are not limited to diagrams, pictures, online quizzes and YouTube videos to creatively present their lessons in the classroom. Different smart board programmes such as the smart notebook, animation, PowerPoint presentations, as well as the show and hide features were also used to enhance creativity. With the help of the smart board, the teachers were also able to use a variety of teaching methods to correct learners' misconceptions and to develop their creative thinking skills. The study recommends that smart boards be utilised as a tool to enhance teachers’ creativity, which ultimately develops learners’ creative thinking skills. Future research may focus on investigating the extent to which smart board features improve learners' creative thinking skills and understanding of various topics.
Thesis (M. (Technology Education)) -- University of Limpopo, 2024
Keywords: Effectiveness; Smart board; Enhancement; Creativity; Creative teaching; Creative thinking; Technology; Teachers; Primary school teachers; School children; Effective teaching -- South Africa; Teaching -- Aids and devices; Technology -- Study and teaching -- Audio-visual aids; Creative ability; Educational technology; Effective teaching -- South Africa -- Mpumalanga